Varieties and interdependencies of demand and growth regimes in finance-dominated capitalism - Franz Prante; Eckhard Hein; Alessandro Bramucci (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
We outline and simulate a stylised post-Keynesian two country stock-flow consistent model to demonstrate the interconnection of three of the main features/outcomes of finance-dominated capitalism, namely worsening income distribution for the bottom 90% households, the rise of international imbalances and the build-up of financial fragility. In the model, twobasic regimesemerge, depending on the institutional setting of the respective model economy:the debt-led private demand boom regime (DLPD) and the export-led mercantilist regime(ELM). We demonstrate the complementarity and interdependence of these two regimesand show how this constellation transformed after the crisis into the domestic demand-led regime (DDL) stabilised by government deficits, on the one hand, andELMregimes, on the other, depending ontherequired deleveraging of private household debt, distributional developments and fiscal policy.
Keywords: B59; E02; E11; E12; E25; E65; F41; O41; 330; post-Keynesian macroeconomics; financialisation; growth regimes; institutions; inequality; debt; stock-flow consistent model